Corrosion Performance of Chemically Passivated and Ion Beam-Treated Austenitic–Martensitic Steel in the Marine Environment - Viktor Semin; Alexander Cherkasov; Konstantin Savkin; Maxim Shandrikov; Evgeniya Khabibova (Journal of Manufacturing and Materials Processing)
In the present work, chemical and ion beam surface treatments were performed in order to modify the electrochemical behavior of industrial austenitic–martensitic steel VNS-5 in 3.5 wt. % NaCl. Immersion for 140 h in a solution containing 0.05 M potassium dichromate and 10% phosphoric acid promotes formation of chromium hydroxides in the outer surface layer. By means of a new type of ion source, based on a high-current pulsed magnetron discharge with injection of electrons from vacuum arc plasma, ion implantation with Ar+ and Cr+ ions of the VNS-5 steel was performed. It has been found that the ion implantation leads to formation of an Fe- and Cr-bearing oxide layer with advanced passivation ability. Moreover, the ion beam-treated steel exhibits a lower corrosion rate (by ~7.8 times) and higher charge transfer resistance in comparison with an initial (mechanically polished) substrate. Comprehensive electrochemical and XPS analysis has shown that a Cr2O3-rich oxide film is able to provide an improved corrosion performance of the steel, while the chromium hydroxides may increase the specific conductivity of the surface layer. A scheme of a charge transfer between the microgalvanic elements was proposed.